Catalytic Effect of Invertase Loaded Glycidyl Methacrylate Copolymer on Inversion of Sugar by Invertase - Srivastava, Sangeeta; Malshe, V.C.; Dave, M.A. (Asian Journal of Chemistry, 2010)
A novel form of invertase covalently `immobilized' on polymer support is proposed as a reusable form of enzyme. Invertase was immobilized on to a copolymer of glycidyl methacrylate and methyl methacrylate. Polymer particles having glycidyl ether groups were prepared through seeded polymerization in aqeous medium. From the HCl-dioxane back titration method, it was found that about 8–10% of oxirane oxygen remained on the final particles. Invertase `immobilised' on copolymer exhibited catalytic effect on sucrose inversion. The prepared immobilized invertase could completely hydrolyze sucrose in water at room temperature, at an enzyme concentration of 0.4% based on sucrose weight having invertase activity 30,000BU/mL. The enzyme was stable under stirred conditions and could be reused multiple times without loss of enzyme activity. It was found that the nature of the polymer used for enzyme conjugation had a significant effect on the activity of the invertase used.